2013
DOI: 10.1124/mol.112.082347
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of ERCC1-XPF Protein-Protein Interaction Synergize Alkylating Agents in Cancer Cells

Abstract: The benefit of cancer chemotherapy based on alkylating agents is limited because of the action of DNA repair enzymes, which mitigate the damage induced by these agents. The interaction between the proteins ERCC1 and XPF involves two major components of the nucleotide excision repair pathway. Here, novel inhibitors of this interaction were identified by virtual screening based on available structures with use of the National Cancer Institute diversity set and a panel of DrugBank small molecules. Subsequently, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
91
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 41 publications
1
91
2
Order By: Relevance
“…2 We sought to identify novel inhibitors of ERCC1-XPF using a high-throughput fluorescencebased in vitro endonuclease assay 3 and one of the hits obtained was compound 1 (Figure 1) with an IC50 value of approximately 30 µM and modest ligand efficiency. The catechol motif is present in known nuclease inhibitors 4 and although the dibromo-substitution and hydrazone motif were considered undesirable, 1 showed good selectivity for ERCC1-XPF in counterscreen assays against the nucleases FEN-1 and DNase I.…”
Section: Introductionmentioning
confidence: 99%
“…2 We sought to identify novel inhibitors of ERCC1-XPF using a high-throughput fluorescencebased in vitro endonuclease assay 3 and one of the hits obtained was compound 1 (Figure 1) with an IC50 value of approximately 30 µM and modest ligand efficiency. The catechol motif is present in known nuclease inhibitors 4 and although the dibromo-substitution and hydrazone motif were considered undesirable, 1 showed good selectivity for ERCC1-XPF in counterscreen assays against the nucleases FEN-1 and DNase I.…”
Section: Introductionmentioning
confidence: 99%
“…117 A virtual screen of potential inhibitors of the ERCC1-XPF interaction using available crystal structures and subsequent in vitro studies in lung, breast, and colon cancer cell lines identified a novel inhibitor of the ERCC1-XPF interaction, NERI02. 118 The specificity of NERI02 remains unclear; however, it has been shown to act synergistically with both cisplatin and mitomycin C (MMC). This may be due to it binding directly with DNA and therefore potentiating platinum sensitivity.…”
Section: Ercc1-xpf Inhibitorsmentioning
confidence: 99%
“…With this limitation, molecular modelling and computer simulations can offer a comprehensive and alternative approach to understand these interactions [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] . Although there have been previous attempts to model the hPD-1/hPD-L1 and hPD-1/hPD-L2 complexes, none of these models correlated well with available experimental data.…”
Section: Research Highlightmentioning
confidence: 99%